MANAGEMEN PENGGUNAAN METODE EDUTAINMENT DALAM PEMBELAJARAN PAI MATERI KISAH TELADAN LUQMAN AL-HAKIM DI SMP SUNAN KALIJOGO JABUNG MALANG - Endang Tyasmaning (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Management of the use of edutainment methods in the learning process includes among others listening, watching, observing, asking, working, discussing, solving problems. For this reason, researchers in a previous study whose essence was the same in the edutainment method but differed in the systematics of the discussion, because each title was not the same but essentially the same in a method to be studied, because it aimed to answer each of the problem formulations which included a method. edutainment in each title, both systematic and this type of research uses qualitative research. five aspects of management in the use of edutainment methods at SMP Sunan Kalijogo Jabung Malang: 1. Planning. 2. Organizing. 3. Implementation. 4. Supervision, and 5. Evaluation.